The effect of early versus delayed challenge after vaccination in controlling SHIV 89.6P infection - Chavez, Leslie L. (2008)
We sought to determine how effectively a CD8(+) T cell inducing vaccine controls SHIV-89.6P infection in rhesus macaques at a range of challenge times post-vaccination. To this end, twenty eight Mamu-A*01(+) rhesus macaques were given replication incompetent human serotype 5 adenovirus vector expressing SIVmac239 gag DNA and boosted 24 weeks later. Groups of 4 monkeys were then challenged with SHIV-89.6P at 1, 3, 6, 12, and 24 weeks after the boost. We compared the kinetics of viral load, CD4(+) and virus-specific CD8(+) T cells in these macaques. Measurements of CD8(+) T cells taken before challenge show an exponential decay between 1 and 12 weeks following vaccination (p<0.0001). After week 12, no further decay was observed. Twenty of 24 vaccinated animals maintained more CD4(+) T cells and kept their viral load at least one order of magnitude lower than the control animals throughout the chronic phase of the study. All 24 vaccinated animals survived the duration of the study. The viral and T cell kinetics over the first two weeks differed between the vaccinated groups, with more recent vaccination improving the early control of virus (p-value = 0.027). The rates of virus specific CD8(+) T cell expansion were greater in animals having higher viral loads at one week (r=0.45, p = 0.029), suggesting that the kinetics of early viral load may have a role in virus specific CD8(+) T cell generation, although these early differences did not lead to different clinical outcomes within the vaccinated animals.